La actividad física como medio para prevenir el sedentarismo en niños del séptimo “A” de la Escuela de Educación Básica “Rosa Josefina Burneo de Burneo”, Loja 2023-2024. - Lima Avila, Ruben David (2025)
This curricular integration work was developed with the main goal of promoting physical activity as a mean to prevent sedentary lifestyle in children of the seventh “A” of the “Rosa Josefina Burneo de Burneo” Basic Education School, 2023-2024. In addition, a mixed approach was used, with a quasi-experimental and correlational design. Relying on inductive, deductive, scientific, historical and analytical methods. Similarly, diagnostic instruments such as a survey and test were applied to a sample of 20 students. According to the results obtained once the diagnostic instruments were applied, it is evident that the test values are high, therefore, based on these results, a pedagogical proposal based on physical activity was designed and applied to prevent sedentary lifestyle in the sample mentioned before, which was structured in 22 class sessions with activities related to the fundamentals of various sports in the sports practice space of the physical education area. After having carried out aerobic activities, recreational and collaborative games focused on different sports, resistance and coordination circuits, and also having increased the time dedicated to carrying out physical activities weekly, it was determined that pulses and heart rate decreased, evidencing improvement in the values and performance of the participants. It is concluded that before the application of the proposal there were some gaps such as the lack of commitment to carry out physical activities and little information about its importance, however, after application of the proposal it is determined that it is effective and has a positive impact on the prevention of sedentary lifestyle and this is reflected in the improvement of physical condition and motivation when performing physical activity. Keywords: Physical activity, sedentary lifestyle, aerobic resistance, educational games, motivation, sports practices.